2021
DOI: 10.1002/jpen.2048
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity and Visceral Fat on Mortality in Hematopoietic Stem Cell Transplantation

Abstract: Rationale: Many studies have shown the importance of body composition parameters, muscle, and fat mass, evaluated by several methods in hematopoietic stem cell transplantation (HSCT) outcomes. Ultrasound (US) is an efficient and low-cost method to evaluate body composition, even though there have not been many studies in HSCT. Objectives: Our goal was to investigate the muscle, visceral fat (VF), and echogenicity before HSCT and after engraftment, evaluated by US and its association with outcomes. Methods: All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Higher echogenicity and lower muscle stiffness were associated with a higher BMI in the deltoid. The association of higher BMI and higher echogenicity is expected [ 38 ] but the predilection to the deltoid is interesting and warrants further study. Apart from the expected greater muscle bulk in the deltoid in males, there were no gender-related differences in muscle stiffness or other US measures in other muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Higher echogenicity and lower muscle stiffness were associated with a higher BMI in the deltoid. The association of higher BMI and higher echogenicity is expected [ 38 ] but the predilection to the deltoid is interesting and warrants further study. Apart from the expected greater muscle bulk in the deltoid in males, there were no gender-related differences in muscle stiffness or other US measures in other muscles.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of allo-HSCT, we have recently demonstrated that mice with dietinduced obesity (DIO) placed on high-fat (HF) diets developed more severe acute GVHD due in part to the induction of a heightened pro-inflammatory cytokine storm (4). These effects were also observed clinically in high-BMI HSCT recipients (4)(5)(6)(7). Interestingly, it was also observed that obesity resulted in restricted microbiome diversity and increased gut permeability, which may account for the specific targeting of the gut for acute GVHD attack (4,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…6 Nutritional sequelae such as obesity, malnutrition and sarcopenia impact and predict HCT outcomes. Obesity pre-HCT is increasingly prevalent 7 negatively predicting 100-day readmission, nonrelapse mortality 8,9 and Graft-versus-Host Disease (GvHD) rates. 8 Malnutrition, defined as undernutrition in this context, impacts treatment outcome, length of admissions, infectious complications, 9 fatigue and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity pre-HCT is increasingly prevalent 7 negatively predicting 100-day readmission, nonrelapse mortality 8,9 and Graft-versus-Host Disease (GvHD) rates. 8 Malnutrition, defined as undernutrition in this context, impacts treatment outcome, length of admissions, infectious complications, 9 fatigue and quality of life. 10 Additionally, secondary sarcopenia, a loss of skeletal muscle mass associated with cancer related inflammation and nutritional deficiencies, 11 is an independent negative prognostic indicator for HCT outcomes.…”
Section: Introductionmentioning
confidence: 99%